Simplify 5a−8c+b+3c−9a+6b.(1 point)

1 answer

To simplify the expression \(5a - 8c + b + 3c - 9a + 6b\), we can combine like terms.

  1. Group the terms:

    • For \(a\): \(5a - 9a\)
    • For \(b\): \(b + 6b\)
    • For \(c\): \(-8c + 3c\)
  2. Combine the coefficients:

    • \(5a - 9a = -4a\)
    • \(b + 6b = 7b\)
    • \(-8c + 3c = -5c\)
  3. Put it all together: \[ -4a + 7b - 5c \]

So the simplified expression is \(-4a + 7b - 5c\).

Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions